Repurposing of N-Acetylcysteine for the Treatment of Dengue Virus-Induced Acute Liver Failure - Tafere GG (Dove Medical Press, 2020)
Gebrehiwot Gebremedhin Tafere, Dawit Zewdu Wondafrash, Filmon Beyenne Demoz Department of Pharmacology and Toxicology, School of Pharmacy, Mekelle University, Mekelle, EthiopiaCorrespondence: Gebrehiwot Gebremedhin Tafere P.O. Box: 1871, Mekelle, EthiopiaTel +251-908822323Email gebrehiwotg07@gmail.comAbstract: The prevalence of dengue infection-induced acute liver damage is increasing from time to time. Since it has no specific antiviral treatment in the world, people in endemic areas suffer more from dengue disorders. Thus, there is a need for searching options for the treatment of dengue-induced acute liver failure. N-acetylcysteine, which is used for the treatment of nasal congestion disorder and paracetamol overdose toxicity, could be used as a definitive therapy for dengue virus-induced acute liver disease. Therefore, this review discusses the therapeutic use of N-acetylcysteine for dengue-induced acute liver disease. Various case reports and case series showed that patients received NAC recovered from their clinical status. Additionally, a preclinical study showed that N-acetylcysteine has anti-dengue virus activity. Thus, N-acetylcysteine could be used as a definitive therapy in dengue virus-induced hepatitis. This might encourage researchers to further investigate the importance of N-acetylcysteine for dengue virus-induced hepatitis.Keywords: N-acetylcysteine, dengue virus, acute liver failure